2003
DOI: 10.1128/jcm.41.8.3757-3764.2003
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Cytomegalovirus Infection in Solid-Organ Transplant Recipients by an Ultrasensitive Plasma PCR Assay

Abstract: Early and accurate monitoring of cytomegalovirus (CMV) infection in solid-organ transplant recipients is of major importance. We have assessed the potential benefit of an ultrasensitive plasma-based PCR assay for renal transplant recipients. The pp65 CMV antigen (pp65 Ag) assay using leukocytes was employed as a routine test for the monitoring of CMV in 23 transplant recipients. We compared the pp65 antigenemia with the CMV load quantified by an ultrasensitive PCR (US-PCR) with a limit of detection of 20 CMV D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
6
25
0
Order By: Relevance
“…In our study, the levels of viral DNAemia were those actually detected prior to the start of preemptive therapy, which prevented consistently HCMV disease and, thus, were verified as safe clinically. Cutoffs proposed by another group taking care of the patient clinical outcome were more similar to those calculated in the present study [Hadaya et al, 2003].…”
Section: Discussionsupporting
confidence: 52%
“…In our study, the levels of viral DNAemia were those actually detected prior to the start of preemptive therapy, which prevented consistently HCMV disease and, thus, were verified as safe clinically. Cutoffs proposed by another group taking care of the patient clinical outcome were more similar to those calculated in the present study [Hadaya et al, 2003].…”
Section: Discussionsupporting
confidence: 52%
“…Other studies, however, have reported a significantly lower sensitivity of antigenemia testing than those of molecular tests (80,88,(94)(95)(96)(97)(98)(99). In one study, the sensitivity of pp65 antigenemia was lower (39%) than that of an ultrasensitive PCR-based assay performed on plasma (67%) (96). Moreover, the LDT plasma PCR assay detected CMV infection 12 days earlier than the antigenemia test (96).…”
Section: Antigen Testingmentioning
confidence: 83%
“…One of these studies reported a strong correlation between pp65 antigenemia and CMV PCR performed on whole-blood specimens by use of an in-house laboratory-developed test (LDT) (91). Other studies, however, have reported a significantly lower sensitivity of antigenemia testing than those of molecular tests (80,88,(94)(95)(96)(97)(98)(99). In one study, the sensitivity of pp65 antigenemia was lower (39%) than that of an ultrasensitive PCR-based assay performed on plasma (67%) (96).…”
Section: Antigen Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both methods have been previously described. 18,19 Preemptive ganciclovir therapy was given at a dose of 5 mg/kg intravenously twice a day for 14 days and then 5 mg/kg daily for 2 weeks. In patients with neutropenia, foscarnet at a dose 90 mg/kg intravenously twice a day for 2 weeks and then 90 mg/kg daily 2 weeks was used.…”
Section: CMVmentioning
confidence: 99%